A mathematical verification on a developed model of ECG wave. (1st October 2010) - Chakraborty, B.; Bera, S.C.
The beating of the heart generates ECG wave from which clinical condition of the heart is analysed. In the present work, a mathematical test has been performed to verify a developed mathematical model of ECG wave. It has been observed that the ECG wave spectral amplitude pattern obtained from the model has almost similar waveform as that obtained from a recorded ECG wave of a normal subject. Also, the ECG wave that is obtained from the model considering arbitrarily selected body parameters and typical body parameters almost resemble a normal ECG wave. Thus the developed mathematical model is verified.